Relationship of demographic profiles and organizational culture with the public service motivation of employees in selected government agencies - Rodriguez, Anna Virgilia V. (Animo Repository, 2018)
Researchers gained interest on the phenomenon about public service motivation among employees in the public sector as it was observed that they have different motivational needs for wanting to serve in the public. Public Service Motivation (PSM) refers to the motive of the individual to serve the public interest that relates to one’s sense and duty to serve the government and society, or an attraction to serve the public for various reasons, regardless as it is for altruistic or for self-centered purposes (Bright, 2016). Given that there are negative impressions on the reputation of public service in the local setting, the researcher investigated the characteristics of the public service motivation of employees in the selected government agencies in Metro Manila. This research study explored the significant relationships of demographic profiles of the employees (i.e, gender/sex, age, marital status, job category, and tenure) and the organizational culture of the selected agencies (i.e, adhocracy, clan, hierarchy, and market type) with the level and types of public service motivation (i.e, instrumental, values-based, and identification). The actual data collected from 820 employees in 18 different government agencies in Metro Manila showed that female, older, single, and management level employees are likely to display high level of public service motivation. There were also significant differences in the public service motivation of employees based on one’s gender/sex, age, and marital status while it remained similar in terms of job category and tenure. Research findings also concluded that employees were likely to develop higher level of public service motivation if they belong in a clan culture type of organization. Likewise, human resources interventions were recommended to incorporate concepts of public service motivation and organizational culture into some HR activities such as recruitment, selection, training and development, succession planning, coaching and mentoring programs, among others.